Clinical outcomes of endoscopic treatment for gastric gastrointestinal stromal tumors: a single-center study of 240 cases in China. (3rd August 2022) - Wang, Deqiong; Ding, Qiang; Cao, Li; Feng, Xinxia; Zhang, Zerui; Lu, Panpan; Ji, Xiaoyu; Li, Lili; Tian, Dean; Liu, Mei
Abstract: Background and aims: Endoscopic resection (ER) gradually becomes an important treatment method for gastrointestinal stromal tumors (GISTs). The aim of this study is to evaluate the efficacy and safety of ER of gastric GISTs. Methods: This retrospective study included 240 patients with gastric GISTs who underwent ER at Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology from January 2010 to December 2019. The clinicopathologic, endoscopic and follow-up data of the patients were collected and analyzed. Results: The mean maximum tumor diameter was 1.67 ± 1.00 cm (range 0.2–6.5 cm), of which 156 cases (65.00%) were small gastric GISTs (tumor diameter < 2 cm). A total of 43 patients (17.92%) had perioperative bleeding, including 40 cases (16.67%) of minor bleeding and three cases (1.25%) of major bleeding. Perioperative perforation occurred in 101 patients (42.08%), of which 51 patients (21.25%) were active perforation and 50 patients (20.83%) were passive perforation. The en bloc resection rate was 97.08% (233/240), and seven cases (2.92%) had piecemeal resection. There were three cases (1.92%) of small gastric GISTs at intermediate risk and one case (0.64%) at high risk. A total of 193 patients were followed up, and no tumor residual, recurrence or metastasis occurred within a median follow-up time of 30 months (range 1–127 months). Conclusions: Endoscopic treatment for gastric GISTs is safe and effective. Piecemeal resection does not seem to be related to the patient's prognosis. Endoscopic resection can be performed if patients are willing to remove small gastric GISTs.